Prinsip Pemeberdayaan Masyarakat Dalam Perspektif Timur dan Barat - Kahar,; Mustari Mustafa,; Sakaruddin Mandjarreki, (Jurnal Berita Sosial, 2024)
This research aims to find out and explore the thoughts of Murtadha Muthahhari and Paulo Freire in Islamic community empowerment in the context of Indonesia and the principles of Pancasila. The research method used in the study entitled “Principles of Community Empowerment in Eastern and Western Perspectives” is the library research method. This method includes data collection activities through relevant literature, such as books, journals, research reports, and other written documents, to understand and analyze the principles of community empowerment in Eastern and Western perspectives. The results of the research on “Principles of Community Empowerment in Eastern and Western Perspectives” show that both perspectives have fundamental differences but also similarities in the ultimate goal of community empowerment. The Eastern perspective, which is influenced by cultural and spiritual values, and thinking emphasizes a harmonious approach, prioritizing local wisdom and social collectivity in building community welfare. Empowerment here is seen as an effort to help individuals develop their potential within the framework of strong social values. In contrast, the Western perspective, particularly the thinking of Paulo Freire, focuses on critical education and social transformation. Paulo Freire proposes empowerment through education that encourages people to actively participate in identifying and addressing their problems.